Sarcopenia in idiopathic pulmonary fibrosis: an updated systematic review and meta-analysis - Zeng, Jun; Liu, Jia; He, Liqian; Zhu, Jianyu; He, Jie; Jiang, Jiaqing; Chen, Zhenglin; Zhu, Xinrui; He, Jia; Yang, Jingyue; Yuan, Yifan (Frontiers in Medicine, 2025)
BackgroundSarcopenia has frequently been identified as a comorbid condition in numerous diseases, ultimately influencing patient outcomes. Nonetheless, within the context of idiopathic pulmonary fibrosis (IPF), it has received relatively insufficient clinical focus. This systematic review and meta-analysis were conducted to estimate the prevalence of sarcopenia among individuals diagnosed with IPF and to investigate the links between sarcopenia and both pulmonary function and prognosis in this population.MethodsComprehensive literature searches were carried out in Excerpta Medica Database (Embase), PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Cochrane Library databases up to 7 July 2025, utilizing relevant MeSH terms. Quality evaluation was implemented through the Joanna Briggs Institute (JBI) tool and the Newcastle-Ottawa Scale. To account for heterogeneity across studies, a random-effects model was implemented. Statistical heterogeneity was examined utilizing I2 statistics. The overall prevalence of sarcopenia was calculated by pooling data to generate percentages accompanied by 95% confidence intervals (CI). For continuous variables sharing identical units, weighted mean differences were adopted as effect size metrics.ResultsIn total, 15 studies satisfied the eligibility requirements for inclusion. Findings indicated that sarcopenia was present in 25% of IPF cases. Participants were stratified into subgroups based on factors such as ethnicity, age, and diagnostic standards for sarcopenia to facilitate subgroup meta-analyses. A consistently elevated prevalence of sarcopenia was observed across all subgroup classifications. Furthermore, most parameters used to assess sarcopenia were found to be decreased in IPF individuals, and those with sarcopenia demonstrated impaired pulmonary function, reduced exercise capacity, and an overall worse prognosis.ConclusionCurrent evidence supports the notion that sarcopenia is highly prevalent in IPF populations and may be closely linked to pulmonary functional impairment. Therefore, early identification and therapeutic intervention of sarcopenia should be emphasized in individuals with IPF. Moreover, standardized sarcopenia diagnostic criteria and protocols are urgently needed to ensure accurate meta-analysis results and research conclusions. A prospective, multicenter prospective study with inclusion of sex-specific and comorbidity-adjusted analyses should be awaited in the future.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251089889, identifier CRD420251089889.